Contemporary issues in applied and professional ethics - Grix, Marco; Dare, Tim, LLB (Research in ethical issues in organizations ;, 2016)
The latest volume of Research in Ethical Issues in Organizations addresses a range of contemporary issues in applied and professional ethics and explores the unique role of organizational ethics in creating and sustaining a pluralistic, free enterprise economy. It is ideally suited to researchers, postgraduates and professionals whose interests include such key issues as tax avoidance, global justice, information sharing and corporate privacy.